The Customer Engagement Effect on Customer Satisfaction and Brand Trust and Its Impact on Brand Loyalty - Meylani Tuti; Viki Sulistia (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: The research purpose is to determine the influence of customer engagement on brand loyalty through customer satisfaction and brand trust.Design/Methodology/Approach: The population in this research was customers who made purchases from December 2019 until February 2020. The sampling technique employed purposive sampling to decide on 200 respondents. The data had been examined for reliability and validity. The data analysis method used quantitative and descriptive. Structural Equation Modeling (SEM) was utilized in the quantitative analysis.Research findings: The research results uncovered that customer engagement significantly influenced customer satisfaction. Customer engagement gave a significant influence on brand trust. Customer engagement gave a significant influence on brand loyalty. Customer satisfaction gave a significant influence on brand trust. The brand trust gave a significant influence on brand loyalty. Customer engagement gave an indirect influence on brand trust through customer satisfaction. Also, customer engagement indirectly influenced brand loyalty through brand trust and customer satisfaction.Theoretical contribution/Originality: The study gives contribution to the growth of brand literature.Practitioner/Policy implication: The study has implications for researchers and sellers on how to improve the brand.Research limitation/Implication: The limitation of this study is that it only used one clothing entrepreneurship business brand that utilized Instagram as a promotional medium for further research. Developing the research object further by using more similar brands is recommended.